(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
River terraces are one of the typical and widespread Quaternary fluvial landforms in Latvia. Until recently, distinguishing and mapping of these features have required extensive field surveys. However, the availability of high resolution digital elevation models (DEM) derived from airborne laser altimetry and application of modern geographic information systems (GIS) provides sufficient background to resolve these tasks. In this study, we apply an integrated methodology based on using of remote sensing, i.e. laser scanning or Light Detection and Ranging (LiDAR) data and combining of semi-automated TerEx tools for the detection of fluvial terraces in DEM. The empirical tests performed using the tools in the study area reveal that the application of TerEx gives the reliable results. However, presence of minor landforms which increase the topographical roughness of the surface directly influence the quality of extracted data, thus leading to the necessity of additional manual editing. The obtained data indicate that the terrace sequence in the Augšdaugava spillway valley consists of eight different terrace levels – T1 to T8. Only terraces T1 and T2 are easily recognizable in the study area, whereas the upper terraces do not have explicit edges.